Gen Z and the SDGs: Leveraging Youth Power for Responsible Consumption in Developing Nations - Linh , Tran Thi My; Doan, Hoang (Journal of Scientific Insights, 2025)
This study explores the evolution of green consumption behavior among Generation Z (Gen Z) in developing countries over the period from 2010 to 2024. Utilizing a synthesis analysis of secondary data from international reports, academic studies, and statistical databases, the research traces the shift in Gen Z’s environmental awareness and sustainable purchasing practices. Findings indicate a significant rise in green consumption trends, particularly since 2015, driven by factors such as social media influence, price affordability, and environmental education. Regional variations are evident: Asia showcases the pivotal role of digital platforms, Latin America benefits from policy-driven education initiatives, and Africa features emerging grassroots movements amid infrastructural challenges. The study highlights Gen Z’s potential as a transformative force in sustainable consumption, though their behavior remains conditional on economic and systemic support. These insights are linked to Sustainable Development Goals SDGs 12 and SDGs13, emphasizing the need for targeted policies to enhance Gen Z’s contribution to global sustainability efforts in developing economies.